THE INFLUENCE OF EMPLOYEE TRAINING, COMPENSATION AND EMPLOYEE CREATIVITY ON INNOVATIVE BEHAVIOR - Maulana, Ramli; Wijanarko, Adrian Azhar (LPPM STIE Muhammadiah Bandung, 2023)
The existence of companies in the era of modernization really requires innovation to be able to compete. By using innovation, companies can provide better service to consumers and add value to the products they produce. PT. Jakarta Transportation has company values which encourage creativity summarized in the tagline